Hak Asasi Manusia Dalam Perspektif Islam - Putri, Audina; Amanda, Dea; Yanti, Rizki Febri; Amin, Afriadi; Batubara, Abdul Karim (Al-Wasathiyah: Journal of Islamic Studies, 2023)
Human rights or what is often abbreviated as HAM in Indonesia have been alluded to in the formulation of the text of the 1945 Constitution of the Republic of Indonesia. Human rights are moral norms or principles that describe standards of human behavior that are systematically protected as human rights law. nationally or internationally. Human rights are generally understood as rights that absolutely become basic rights where people inherently have rights because of their position as human beings which include aspects of their nation, location, language, religion, ethnicity, and other statuses. Based on searching the verses of the Al-Qur'an and As-Sunnah, it is concluded that Islamic law has formulated the regulation and protection of human rights for humans.